Marikina safe haven community center and livelihood support facility - Matienzo, Josiah Ned P.; Boot, Luis Ma. T. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The local footwear manufacturing industry defined the economic identity of Marikina for decades. Due to the intensified effects of globalism in the local market, the local footwear products are struggling to compete with international brands. As an architectural response, the Marikina Safe Haven aims to host the initiatives of the local government to execute projects that range from capacity development of the ship-owners and their employees, to technology development in the design and production of footwear products. Marikina Safe Haven is a community center where people could congregate and organize community building activities specially those events that help the shoe industry such as the annual Shoe Expo and Trade Fair. Another threat to the city's well-being is their vulnerability to natural calamities. Close proximity to the West Valley Fault makes the susceptible to earthquakes, and landslides caused by earth-shaking. On top of that, the city is also vulnerable to flooding due to its low level elevation. As a response, the Marikina Safe Haven is designed to be utilized as a temporary evacuation center in times of these natural disasters. With having two major functions (supporting the local industry and accommodating evacuees) the facility's utilization is optimized.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Community centers; Community centers -- Marikina -- Philippines